STRATEGI KEPEMIMPINAN KEPALA MADRASAH DALAM MENINGKATKAN PROFESIONALISME GURU - Abdul Rosyid (LPPM Universitas Islam 45, 2023)
This study aims to determine the leadership of the Sulamul Huda Ibtidaiyah Madrasah principal in improving teacher professional competence, the efforts made and the inhibiting factors that exist in Sulamul Huda Bojonggede Madrasah Ibtidaiyah, Bogor Regency. The research method uses a qualitative approach with data collection techniques through interviews, observation and documentation. The results of this study indicate that the understanding of the Head of Madrasa Ibtidaiyah Sulamul Huda about teacher professionalism is the teacher's commitment to carry out tasks according to ability and always improve their qualifications and competencies to realize the vision and mission of the madrasa and national education goals, the efforts made by the head of Madrasa Ibtidaiyah Sulamul Huda in increasing professionalism teachers is optimizing their duties and functions as educators, managers, administrators, supervisors, leaders, innovators and motivators. The leadership strategy of the Sulamul Huda Ibtidaiyah Madrasa principal in increasing professionalism by implementing a strategy in the form of a human-oriented leadership attitude through a democratic and charismatic attitude which is manifested by listening and clarifying, directing and motivating, explaining and negotiating, exemplifying and providing solutions, measuring and providing reinforcement carried out in an instructive and participatory manner.